The Effect of Gyrotonic Training on Developing Certain Bio-Kinetic Abilities Among Young Shot Putters - Qusay Kadhem Jabbar Ahmed (Musamus Journal of Physical Education and Sport (MJPES), 2025)
The objective of this research was to devise exercises for Gyrotonic training to develop specific physical and bio-kinetic capabilities for young shot putters consisting of Al-Furat Sports Club as well as to discover if these exercises could enhance their level of performance. The researcher employed the experimental method to satisfy the objectives of the research. The analysis of the data showed the Gyrotonic training program had a role in promoting the strength of the muscle groups involved in the performance of shot put for the young athletes. The use of practical exercise doubled their activity, which in turn developed increased fidelity and a marked improvement in their measurable performance ability. The exercises that were selected were systematically structured to be varied and smooth and customary to athletes’ skill level. The analysis also showed a significant increase in overall performance of the shot put after the implementation of Gyrotonic training to young athletes. The researcher highly recommends the implementation of exercises using Gyrotonic training for each sport and event. Additionally, the researcher recommends future studies to fully utilize Gyrotonic training and develop it into a competitive methodology in track and field. The researcher also recommends, if applicable, to simulate performing Gyrotonic training with other technical practice in order to effectively utilize training time and efficiency. Research on this practice in different age populations and sports would expand our understanding of its general application to athletes.